Significant impact of melt-blend and hot-press technique operating condition on polyethylene/thermoplastic starch/aloe vera gel film properties / Siti Fatma Abd Karim ... [et al.] - Abd Karim, Siti Fatma; Jai, Junaidah; Abdol Aziz, Rabiatul Adawiyah; Ku Hamid, Ku Halim (Universiti Teknologi MARA Shah Alam, 2023)
Melt-blend and hot-press techniques were among the most popular methods for producing polyethylene/thermoplastic starch (PE/TPS) polymer blends. However, different operating conditions contributed to the various quality of film made. Thus, this paper focuses on determining the most suitable operating conditions involving melt-blend and hot-press techniques on specific PE/TPS/aloe vera gel (AV) film formulations. Thus, this study determines the best operating condition for producing PE/TPS/AV blend. One-factor-at-a-time (OFAT) method was implemented under six operating conditions: different melt-blending temperatures, pre-heating, hot-pressing pressure, temperature and duration, and cooling application. The result demonstrated that the best melt-blending temperature was 170 °C, having the highest tensile strength (TS) performance. Pre-heating application reduced the thickness, which is suitable for applying single-used plastic and more economical than thicker film. Importantly, this study found the lowest pressure to obtain a smooth surface of film without stickiness during the peeling process from the steel plate after applying the hot-press technique. The same condition faced at 130 °C, hot-pressing temperature produced a smooth and clear film structure. The pro-longed hot-pressing duration reduced the bonding strength of the polymer matrix. Finally, a fast-cooling rate enhances the TS of the film. Therefore, the melt-blending and hot-pressing operating conditions significantly impact the physical and mechanical properties of PE/TPS/AV film. The results of this study are valuable for understanding that each formulation needs a specific processing condition essential as an initial assumption in simulation processes.